2021
DOI: 10.21608/ejchem.2021.102664.4755
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Docking and DFT Study of Synthesized Oxazine Derivatives

Abstract: Molecular docking and DFT calculation have been investigated for the synthesized oxazine derivatives. Theoretical calculations including DFT study has investigated and proved the reactivity of compound 4 is the greatest among others as follow 4>2>5>3>1. On the other hand, the stability of compounds has been calculated to prove that compound 1 has the highest stability among others as follow 1>3>5>2>4. Antibacterial activity test was confirmed potent activity for all the synthesized derivatives against E. coli … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Soft molecules are more reactive and more likely to interact with biological target macromolecules than hard molecules. 48 , 49 Hence, it can be inferred that nimbidiol may be the most reactive phytochemical as compared to nimbidic acid, desacetylnimbinolide, O-methylazadironolide, and desflurane-6α-hydroxyazadiradione. In terms of the chemical potential feature of the compounds, those with higher chemical potential value show lower stability and higher reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…Soft molecules are more reactive and more likely to interact with biological target macromolecules than hard molecules. 48 , 49 Hence, it can be inferred that nimbidiol may be the most reactive phytochemical as compared to nimbidic acid, desacetylnimbinolide, O-methylazadironolide, and desflurane-6α-hydroxyazadiradione. In terms of the chemical potential feature of the compounds, those with higher chemical potential value show lower stability and higher reactivity.…”
Section: Resultsmentioning
confidence: 99%
“…The overall electronic energy value of a synthesized bis amide is -34694.5 eV. The dipole moment is 10.4 Debye, E-HOMO), (E-LUMO) and (∆E) is -6.2254, -2.85093 and 3.37447 eV respectively, Negative values of E-HOMO) and (E-LUMO) it showed that the bis amide is thermodynamically stable [33,34], the HOMO orbitals are distributed over the amide group and toluidine moieties and LUMO orbitals are mainly distributed over meta-nitro phenyl moieties. In the MEP map the red area represents the electronegative region and the blue area represents the electropositive region C, and H lies in the blue region, where O and N lie in the red region [35].…”
Section: Dft Studymentioning
confidence: 92%
“…They reported that five compounds of newly synthesized have IC 50 values less than 5.95 µM. In our continuous attempts to develop novel potent bioactive agents ( Abdel-Jalil et al, 2015 , El-ajaily et al, 2019 , El-Barasi et al, 2020 , Eleya et al, 2011 , Hussain et al, 2008 , Ibad et al, 2011 , Kamel et al, 2022a , Kamel et al, 2022b , Mahal, 2015a , Mahal et al, 2010 , Mahal et al, 2011 , Mahal et al, 2015b , Mahal et al, 2015c , Mahal et al, 2019 , Mahal et al, 2021 , Marzano et al, 2022 , Mohapatra et al, 2021 , Salman et al, 2011 , Salman et al, 2020 , Salman et al, 2022 , Yang et al, 2017 , Yang et al, 2018 , Zinad et al, 2020a , Zinad et al, 2020b , Zinad et al, 2020c , Zinad et al, 2020d , Zinad et al, 2021a , Zinad et al, 2021b , Zinad et al, 2022 , Zinad et al, 2023a , Zinad et al, 2023b ), we aim at this study to investigate the molecular docking and DFT calculation of potent anticancer agents of tetrahydrocurcumin.…”
Section: Introductionmentioning
confidence: 99%